Effect of non-destructive edible coating materials and refrigerated storage on quality and shelf life of bell pepper (Capsicum annuum) - KUMAR, NAVEEN; THAKUR, K S; DEVI, KAVITA; KUMAR, SATISH (The Indian Journal of Agricultural Sciences, 2022)
Bell pepper (Capsicum annuum L.) has high nutritional value but the high water content makes it susceptible to water loss and shrivelling, limiting the storage life. The present investigation was carried out at the post-harvest physiology laboratory of Dr Y S Parmar University of Horticulture and Forestry, Nauni, Himachal Pradesh in 2017–18 to evaluate the effect of various edible coatings on the quality of capsicum fruits. Comparative mean analysis by Tukey’s test (P